2018
DOI: 10.1186/s12933-018-0784-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous exenatide infusion for perioperative blood glucose control on myocardial ischemia-reperfusion injuries after coronary artery bypass graft surgery: sub study of the phase II/III ExSTRESS randomized trial

Abstract: BackgroundThe aim of the study was to investigate whether intravenous (iv) infusion of exenatide, a synthetic GLP-1 receptor agonist, could provide a protective effect against myocardial ischemia-reperfusion injury after coronary artery bypass graft (CABG) surgery.MethodsA sub study analysis of patients > 18 years admitted for elective CABG and included in the ExSTRESS trial was conducted. Patients were randomized to receive either iv exenatide (1-h bolus of 0.05 µg min−1 followed by a constant infusion of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
(72 reference statements)
2
15
0
Order By: Relevance
“…In the present study, the most statistically robust findings were also the higher heart rates observed in the liraglutide group. This effect has been consistently demonstrated in previous studies [16][17][18][19] and GLP-1 receptors have been found in the sinoatrial node [10,20,21]. Some authors have found GLP-1 RAs to induce vasodilation and microvascular recruitment, resulting in lower systemic vascular resistance [21] as well as an atrial natriuretic peptide-mediated reduction of systolic and diastolic blood pressures [4].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, the most statistically robust findings were also the higher heart rates observed in the liraglutide group. This effect has been consistently demonstrated in previous studies [16][17][18][19] and GLP-1 receptors have been found in the sinoatrial node [10,20,21]. Some authors have found GLP-1 RAs to induce vasodilation and microvascular recruitment, resulting in lower systemic vascular resistance [21] as well as an atrial natriuretic peptide-mediated reduction of systolic and diastolic blood pressures [4].…”
Section: Discussionsupporting
confidence: 76%
“…While we performed the first randomised trial using liraglutide in patients undergoing cardiac surgery [2], Besch et al randomised patients undergoing CABG to either a continuous exenatide infusion or insulin for glycaemic control [16]. Similar to our present study, the authors performed an analysis of cardiac outcomes and found no difference in postoperative troponin levels nor in the incidence of reduced left ventricular ejection fraction between treatment and control groups [17]. Of note, the primary outcome of this trial (time spent within the glycaemic target range) also did not reach a significant difference between groups [16].…”
Section: Discussionsupporting
confidence: 72%
“…It protects against acute liver injury in the mouse [57]. However, cardiovascular benefits have not been observed in studies of exenatide [13, 58]. In low-risk patients undergoing scheduled coronary artery bypass grafting surgery, postoperative intravenous exenatide provided no additional cardio-protective effect compared to intravenous insulin [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiovascular benefits have not been observed in studies of exenatide [13, 58]. In low-risk patients undergoing scheduled coronary artery bypass grafting surgery, postoperative intravenous exenatide provided no additional cardio-protective effect compared to intravenous insulin [58]. Therefore, it is still necessary to study the cardiovascular efficacy and safety profile of GLP-1 RAs so as to confirm their place in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the use of dipeptidyl peptidase-4 inhibitors were associated with a reduced risk of heart failure hospitalization compared to GLP-1RAs [24]. Moreover, postoperative exenatide did not provide any additional cardioprotective effect compared to intravenous insulin in coronary artery bypass grafting patients [25]. The effects of GLP-1RA on the cardiovascular risk are still controversial.…”
Section: Discussionmentioning
confidence: 99%